IDENTIFIKASI BATERI PENGIKAT TIMBAL (Pb) PADA SEDIEN DI PERAIRAN SUNGAI SIAK - Sri Wulandari; Nila Fitri Dewi; Suwondo ' (Program Studi Pendidikan Biologi, 2005)
The research done to know bacteria type capable to fasten heavy metal lead (Pb) at sediment in territorial water of Siak River Research procedure consist o f three phase that is; (1) Intake o f sediment sampel by purposive sampling random; (2) Isolation by grow sediment sampel at medium of Zobell 2216 E added with PbNO3 and of Pb(CH3COOH)2 ; (3) Total count of bacteria and identification pursuant to morphology form and biochemical test which cover; colony form, colony colour, colony size measure, cell form, coloration of gram, test katalase, test oksidase and methyl red Result of research indicate that total count of bacteria fastener o f heavy metal of lead (Pb) at sediment in territorial water o f Siak River range from 3,0 X 107 until 1,5 X 10s cell/ml and identified 6 bacterium type fastener of heavy metal of lead (Pb) that is: Micrococcuc, Corynebacterium, Phenylobacterium, Enhydrobacter, Morrcoccuss, Flavobacterium. Key words : Bacteria fastener of heavy metal of lead ( Pb), identification, sediment